An economic evaluation of expanding hookworm control strategies to target the whole community. Issue 1 (December 2015) - Turner, Hugo; Truscott, James; Bettis, Alison; Shuford, Kathryn; Dunn, Julia; Hollingsworth, T.; Brooker, Simon; Anderson, Roy
Abstract Background The WHO treatment guidelines for the soil-transmitted helminths (STH) focus on targeting children for the control of morbidity induced by heavy infections. However, unlike the other STHs, the majority of hookworm infections are harboured by adults. This untreated burden may have important implications for controlling both hookworm's morbidity and transmission. This is particularly significant in the context of the increased interest in investigating STH elimination strategies. Methods We used a deterministic STH transmission model and parameter estimates derived from field epidemiological studies to evaluate the impact of child-targeted (2–14 year olds) versus community-wide treatment against hookworm in terms of preventing morbidity and the timeframe for breaking transmission. Furthermore, we investigated how mass treatment may influence the long-term programmatic costs of preventive chemotherapy for hookworm. Results The model projected that a large proportion of the overall morbidity due to hookworm was unaffected by the current child-targeted strategy. Furthermore, driving worm burdens to levels low enough to potentially break transmission was only possible when using community-wide treatment. Due to these projected reductions in programme duration, it was possible for community-wide treatment to generate cost savings – even if it notably increases the annual distribution costs. Conclusions Community-wide treatment is notably more cost-effective for controlling hookworm's morbidity and transmission than the current child-targeted strategies and could even be cost-saving in many settings in the longer term. These calculations suggest that it is not optimum to treat using the same treatment strategies as other STH. Hookworm morbidity and transmission control require community-wide treatment.